Nanoscale investigations of surface phenomena in the water teatment industry using the atomic force microscope - Bargir, Sameer M. (Cranfield University, 2007)
Understanding the interaction between surfaces at the intermolecular level in ambient conditions is not only a fundamental science, but is of increasing value to water treatment systems. Here the uses of the atomic force microscopy (AFM) modified with particles of interest are assessed, and compared to bench-scale experimental techniques. In the first part of this study, the results from force measurements performed with calcite-modified probes in synthetic hard water (SHW) on selected substrates showed there was no correlation with macroscale scaling rate experiments. However, unmodified tips showed some correlation with non-metal substrates, where carbon coatings (Dymon-iC and Graphit-iC) were least adhesive. Although unmodified tips were unlikely to represent one of the surfaces of interest in water treatment systems, the findings suggest they can be used to screen materials with Ra < 50 nm. Contact angle measurements complemented force data, indicating the origin of repulsive forces on carbon coatings was due to hydrophilic repulsion because carbon and calcite were highly basic. Enhanced adhesion was caused by hydrophobic attraction and the presence of acidic surface groups. In the 2nd part of this study, force measurements were performed on natural organic matter (NOM) polyanions such as humic acid fraction (HAF), fulvic acid fraction (FAF) and hydrophilic acid (HPIA) using modified and unmodified tips. The results showed in symmetric NOM-NOM interactions with modified tips, HPIA-HPIA dominated both adhesion and detachment lengths, while FAF-FAF and HAF-HAF gave similar adhesion profiles. It is thought these intermolecular interactions can be transferred to floc size data, where HPIA flocs were bigger than FAF flocs. In non-symmetric systems adhesion between FAF-NOM was indiscriminate, compared to HAF and HPIA polyanions, indicating FAF polyanions were most likely to control coagulation performance during NOM removal.